Evidence of economic policy uncertainty and COVID-19 pandemic on global stock returns - Thomas C. Chiang (Journal of Risk and Financial Management, 2022)
This paper examines the impact of changes in economic policy uncertainty (EPU) and COVID-19 shock on stock returns. Tests of 16 global stock market indices, using monthly data from January 1990 to August 2021, suggest a negative relation between the stock return and a country's EPU. Evidence suggests that a rise in the U.S. EPU causes not only a decline in a country's stock return, but also a negative spillover effect on the global market; however, we cannot find a comparable negative effect from global EPU to U.S. stocks. Evidence suggests that the COVID-19 pandemic has a negative impact that significantly affects stock return worldwide. This study also finds an indirect COVID-19 impact that runs through a change in domestic EPU and, in turn, affects stock return. Evidence shows significant COVID-19 effects that change relative stock returns between the U.S. and global markets, creating a decoupling phenomenon.
Keywords: G11; G12; G15; 330; economic policy uncertainty; COVID-19; equity market volatility; GARCH model; global market; uncertainty premium